Vitamin D receptor is not required for the rapid actions of 1,25-dihydroxyvitamin D3 to increase intracellular calcium and activate protein kinase C in mouse osteoblasts - Wali, Ramesh K.; Kong, Juan; Sitrin, Michael D.; Bissonnette, Marc; Li, Yan Chun (Journal of cellular biochemistry, 2003)
The rapid, non‐genomic actions of 1,25‐dihydroxyvitamin D3 [1,25(OH)2D3] have been well described, however, the role of the nuclear vitamin D receptor (VDR) in this pathway remains unclear. To address this question, we used VDR(+/+) and VDR(−/−) osteoblasts isolated from wild‐type and VDR null mice to study the increase in intracellular calcium ([Ca2+]i) and activation of protein kinase C (PKC) induced by 1,25(OH)2D3. Within 1 min of 1,25(OH)2D3 (100 nM) treatment, an increase of 58 and 53 nM in [Ca2+]i (n = 3) was detected in VDR(+/+) and VDR(−/−) cells, respectively. By 5 min, 1,25(OH)2D3 caused a 2.1‐ and 1.9‐fold increase (n = 6) in the phosphorylation of PKC substrate peptide acetylated‐MBP4–14 in VDR(+/+) and VDR(−/−) osteoblasts. The 1,25(OH)2D3‐induced phosphorylation was abolished by GF109203X, a general PKC inhibitor, in both cell types, confirming that the secosteroid induced PKC activity. Moreover, 1,25(OH)2D3 treatment resulted in the same degree of translocation of PKC‐α and PKC‐δ, but not of PKC‐ζ, from cytosol to plasma membrane in both VDR(+/+) and VDR(−/−) cells. These experiments demonstrate that the 1,25(OH)2D3‐induced rapid increases in [Ca2+]i and PKC activity are neither mediated by, nor dependent upon, a functional nuclear VDR in mouse osteoblasts. Thus, VDR is not essential for these rapid actions of 1,25(OH)2D3 in osteoblasts. © 2003 Wiley‐Liss, Inc.